1994
DOI: 10.1007/bf01739918
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of aTrichosporon beigelii septicemia in a granulocytopenic patient with amphotericin B and granulocyte colony-stimulating factor

Abstract: Invasive fungal infections have become an increasing problem in severely immunocompromised hosts. We here report a case of septicemia, caused by Trichosporon beigelii, an unusual pathogen of systemic infections. This infection was acquired during a period of severe neutropenia after chemotherapy for relapsed acute myelogenous leukemia following allogeneic bone marrow transplantation. The patient recovered from a life-threatening T. beigelii septicemia due to early intensified treatment with amphotericin B and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 12 publications
2
20
0
2
Order By: Relevance
“…The recovery of neutrophil count appears to be the most important factor influencing the outcome of 7: beigelii infection [20]. The results of the present study suggest that ingestion of Trichosporon can be enhanced by GM-CSF -it is not known whether the fungicidal activity of neutrophils is enhanced by cytokines.…”
Section: Discussionmentioning
confidence: 59%
“…The recovery of neutrophil count appears to be the most important factor influencing the outcome of 7: beigelii infection [20]. The results of the present study suggest that ingestion of Trichosporon can be enhanced by GM-CSF -it is not known whether the fungicidal activity of neutrophils is enhanced by cytokines.…”
Section: Discussionmentioning
confidence: 59%
“…Antifungal therapy often fails to induce an improvement in the fungal complication; some authors have suggested that the addition of rhG-CSF or rhGM-CSF, by reducing the neutropenia, favors recovery from infection [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…44 Other antifungal agents, particularly the triazoles, have shown promising activity both in vitro and in vivo against this opportunistic fungal pathogen. 1~ However, the reported clinical experience with triazoles has been limited, 13 and furthermore, since these agents are fungistatic, it has been suggested that trichosporonosis in patients with persistent profound neutropenia may fail to respond to azole alone.…”
Section: Discussionmentioning
confidence: 99%